METTL3 and FTO Regulate Heat Stress Response in Hu Sheep Through Lipid Metabolism via m6A Modification - Bowen Chen; Chao Yuan; Tingting Guo; Jianbin Liu; Zengkui Lu (Animals)
In an established hepatocyte lipid deposition heat stress model, the expression levels of METTL3 and FTO were significantly upregulated (p < 0.05), indicating that METTL3 and FTO play important roles in the process of lipid deposition heat stress in hepatocytes. Transcriptome and metabolome analyses showed that lipid deposition heat stress had significant effects on the linoleic acid, linolenic acid, glycerophospholipid, and arachidonic acid metabolic pathways in hepatocytes. After METTL3 knockdown, the m6A methylation level decreased, but the difference was not significant (p > 0.05), the FABP4 and Accα expression levels increased, and the HSP60, HSP70, and HSP110 expression levels decreased significantly. After METTL3 overexpression, the m6A methylation level increased significantly and the expression levels of FABP4, ATGL, Accα, HSP60, HSP70, HSP90, and HSP110 decreased significantly, indicating that the overexpression of METTL3 reduced the expression of heat shock genes by inhibiting the lipid-deposition-related gene expression in an m6A-dependent manner. The m6A methylation level increased significantly after FTO knockdown, while HSP60, HSP110, FABP4, ATGL, and Accα expression levels were significantly reduced. Following FTO overexpression, the m6A methylation level and HSP60, HSP90, and HSP110 expression levels significantly decreased, while the ATGL and Accα expression levels significantly increased. This indicates that the overexpression of FTO promoted the expression of lipid-deposition-related genes in an m6A-dependent manner to reduce the expression of heat shock genes. Transcriptome and metabolome sequencing screened a large number of differential genes and metabolites, and a KEGG enrichment analysis showed that m6A methylation mainly regulated heat stress by affecting the TNF, cAMP, MAPK, lipolysis, and synthesis pathways in hepatocytes. In the lipid deposition heat stress model of preadipocytes, the regulation of gene expression was similar to that in hepatocytes.